PIUTANG SEBAGAI MEDIASI DALAM STRUKTUR MODAL MEMPENGARUHI RETURN SAHAM PERUSAHAAN PERBANKAN - Umi Murtini (Jurnal Riset Akuntansi dan Keuangan, 2022)
ABSTRACT This study examines the role of receivables as a intervening variable in the capital structure affecting stock returns. The amount of receivables is measured using the natural logarithm of receivables, the capital structure is measured using the debt equity ratio (DER) and the return on shares is measured using annual stock returns. The analysis method is used regression with panel data (pooled data). The regression model is used the Common Effect Model. The research sample was used by banking companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The results showed that receivables supported as a intervening variable in the capital structure affect stock returns. Keywords: DER, receivables, stock return, moderating ABSTRAK Penelitian ini menguji peran piutang sebagai variabel mediasi dalam struktur modal mempengaruhi return saham. Besarnya piutang diukur menggunakan logaritma natural piutang, struktur modal diukur menggunakan debt equity ratio (DER) dan return saham diukur menggunakan return saham tahunan. Metoda analisis digunakan regresi dengan data panel (pooled data). Model regresi digunakan Common Effect Model. Sampel penelitian digunakan perusahaan perbankan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2016-2020. Hasil penelitian menunjukkan bahwa piutang terdukung sebagai variabel mediasi dalam struktur modal mempengaruhi return saham. Kata Kunci: DER, piutang, return saham, pemoderasi